Infrastructure And Development : A Critical Appraisal of The Macro Level Literature - Straub, Stéphane, 1966- 1966- (The World Bank, 2008)
This survey reviews the existing macro-level empirical literature on the link between infrastructure and development outcomes in a critical light. After providing a general framework that casts the relevant terms of the controversy on the real effect of infrastructure on growth in the context of an aggregate production function, it signals what are the relevant empirical questions to be addressed. This guides the systematic review of a number of empirical studies and the discussion of the main econometric challenges to the identification of the effect of infrastructure on output and productivity. Finally, building on related research, in particular in contract theory and political economy, the paper spells out several promising research avenues